Delamination and re-assembly of surfactant-containing Li/Al layered double hydroxides - Singh, Mahua; Ogden, Mark; Parkinson, Gordon; Buckley, Craig; Connolly, Joan (The Royal Society of Chemistry, 2004)
Exchange of the chloride anion intercalated in [LiAl2(OH)6]Cl.nH2O with a range of surfactants is reported. Attempts to delaminate (or exfoliate) the surfactant-exchanged intercalates, where the surfactant was an alkyl sulfate, were unsuccessful. In contrast, delamination of the layered double hydroxides [LiAl2(OH)6][C12H25C6H4SO3.nH2O] and [LiAl2(OH)6][C8H17C6H4SO3.nH2O] was successful. The necessity of the alkyl chain of the surfactants was demonstrated by the failure of [LiAl2(OH)6][CH3C6H4SO3.nH2O] to delaminate. The delamination of the unique Li/Al LDH is thus found to be dependent on the guest surfactant structure in terms of both chain length and head group moiety.